Market orientation of business schools and development of professional competencies of students in the tourism business - Rosi Maja; Jurše Milan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2016)
Recent trends of spreading of market globalization, technological progress, internationalization, privatization and other relevant changes are strategically changing the context in which all institutions of society operate and prosper. The higher education sector is also affected, and, in particular, the business education has to be better aligned with these external realities. In this dynamic and changing environment, students, businesses and other stakeholders require knowledge and skills that will provide them with competency in relation to the current economic situation and technological advances. Tourism sector and whole economy increasingly depend on contemporary knowledge that provides appropriate job competency to students and competitive advantage to the providers of services. Adjustment of public higher education institutions is important for enhancing their market position in increasingly competitive market for business education. There is an increasing number of private business schools that have emerged recently, also in the field of tourism that have seen their great potential for business success and earnings in the increasingly competitive business education market, framed by a very dynamic and competitive environment of business education. In addition, business schools have to deal with the trend of shrinking budgetary (public) funding of their operation, which forces them to search for additional funding by providing new educational offerings and strengthening of their market orientation. In the debate about the future of tourism education, there lies a gap between the requirements of the curriculum and the expectations of the industry, which argues that higher education has to serve the tourism of the future - that is to prepare students for a more active role in tourism organizations and in their search for improvements and adaptation to different competitive circumstances. Does business schools' curriculum follow the development of key recent trends in the industry? The main objective of this paper is to identify the key aspects of the dynamic adaptation of university business schools and to elaborate on the possible linkage between the development of professional competences of students in the field of tourism and the professional requirements of organizations in this industry. We will use the comparative method (overview and comparison of tourist programs of selected faculties in selected countries of the former Yugoslavia, review and comparison of their programs regardless of any possible accreditation) and benchmarking analysis that will help us identify differences in achieved professional student competencies in selected faculties and compare them against achieved professional student competencies of selected, leading faculties in central Europe in the field of tourism.